Design of experiment for micromilling and solvent assisted ultrasonic bonding - Muhammad Hilmi Zainuddin. (2011)
Today, one of the most important fields of interest within the manufacturing arena lies in the fabrication of miniaturized components. There are many available fabrication techniques such as lithography, hot embossing, laser-cutting and micro milling. However, a majority of these techniques lack the versatility that micro milling possesses. Its efficiency and economical means have proven to be a viable option for prototyping and small lot production. Instead of utilizing silicon as a primary material, Polymethyl-methacrylate (PMMA), which possesses good chemical properties, transparency and versatility, was utilized in this experiment. Unlike PMMA, silicon micromachining techniques are expensive, time consuming and require access to special facilities. A design of experiment (based on Central Composite Design) on PMMA micro milling was conducted on two end mill diameters (0.2mm and 0.5mm) to optimize cutting parameters (i.e. step over ratio, spindle speed and feed rate) that will produce minimum surface roughness. A quadratic regression model was developed to fit the experimental data through Design Expert Software, which optimized the parameters. The optimized parameters are (Spindle speed: 12 514rpm, Feed Rate: 1mm/s and Step-Over Ratio: 25%) with an expected surface roughness of 0.425μm for 0.2mm end mill. While the results for 0.5mm end mill are (Spindle Speed: 15345rpm, Feed Rate: 2.78 and Step-Over Ratio: 25%). A design of experiment, based on Face Centered Design, was conducted to investigate bond shear strength for solvent assisted ultrasonic bonding. However, the gathered results, was limited by material failure as a result of the bond strength being significantly stronger than the material strength.